CellCycleTRACER accounts for cell cycle and volume in mass cytometry data - Maria Anna Rapsomaniki (Nature Portfolio, 2018)
Mass cytometry is a powerful method of single cell analysis, but potential confounding effects of cell cycle and cell volume are not taken into account. Here the authors present a combined experimental and computational method to correct for these effects and reveal features of TNFα stimulation that are otherwise masked.